2021
DOI: 10.11591/ijeecs.v23.i3.pp1681-1688
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of mango leaf disease using convolutional neural network models: a transfer learning approach

Abstract: <p>The acknowledgment of plant diseases assumes an indispensable part in taking infectious prevention measures to improve the quality and amount of harvest yield. Mechanization of plant diseases is a lot advantageous as it decreases the checking work in an enormous cultivated area where mango is planted to a huge extend. Leaves being the food hotspot for plants, the early and precise recognition of leaf diseases is significant. This work focused on grouping and distinguishing the diseases of mango leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In 2021, Rajbongshi et al. concentrated on using CNN to classify and identify the illnesses affecting mango leaves.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, Rajbongshi et al. concentrated on using CNN to classify and identify the illnesses affecting mango leaves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The PMRFO performance is computed with different classifiers like RNN. DBN, GRU, CNN, NNE (Mia et al., 2020), and TLA (Rajbongshi et al., 2021) along with the findings are provided in Table 5. When observing the table, the PMRFO offered better outcomes over the others for mango disease detection.…”
Section: Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In their trial, they discovered that segmentation of anthracnose (fungal) sickness was accurate, with an average specificity of 91.15 % and Sensitivity of 90.86%. Rajbongshi et al [12] employed convolutional neural network models to diagnose mango leaf disease using a transfer learning method. They ought to employ methods like CNN and others to concentrate on more ailments in order to increase accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Adducing the major findings about the viability of employing an in-band scenario for deploying NB-IoT over a 4G network in a suburban setting based on the acquired data. Rajbongshi et al [36], Erwin et al [37] suggested different types of leaf diseases, such as anthracnose, gall machi, powdery mildew, and red rust, are employed in the dataset, which includes 1500 photos of damaged and healthy mango leaves. A new category has been added to the dataset.…”
Section: Related Workmentioning
confidence: 99%